Pengaruh Luas Lahan dan Tenaga Kerja terhadap Produksi Padi di Kabupaten Grobogan Tahun 2015–2024 - Wulandari, Yeni Septiana; Meidy Haviz (UNISBA Press, 2025)
Abstract. Rice production is a pillar of national food security, but in Grobogan Regency, its sustainability is threatened by land conversion and the shift of labor to non-agricultural sectors. This study aims to analyze the influence of land area and labor on rice production in Grobogan Regency during the period 2015–2024. Using a quantitative approach with multiple linear regression, secondary data from the Central Statistics Agency were analyzed using EViews 10, including classical assumption testing and statistical tests. The results indicate that, simultaneously, land area and labor significantly influence rice production. Partially, only labor is significant at the 95% confidence level, while land area is significant at the 90% level. These findings highlight the importance of preserving agricultural land and increasing labor participation as key factors for the sustainability of rice production in this region. Abstrak. Produksi padi merupakan pilar ketahanan pangan nasional, namun di Kabupaten Grobogan, keberlanjutannya terancam oleh alih fungsi lahan dan pergeseran tenaga kerja ke sektor non-pertanian. Penelitian ini bertujuan menganalisis pengaruh luas lahan dan tenaga kerja terhadap produksi padi di Kabupaten Grobogan periode 2015-2024. Menggunakan pendekatan kuantitatif dengan metode regresi linier berganda, data sekunder dari Badan Pusat Statistik dianalisis menggunakan EViews 10, meliputi pengujian asumsi klasik dan uji statistik. Hasil menunjukkan bahwa secara simultan, luas lahan dan tenaga kerja berpengaruh signifikan terhadap produksi padi. Secara parsial, hanya tenaga kerja yang signifikan pada tingkat kepercayaan 95%, sementara luas lahan signifikan pada 90%. Temuan ini mengindikasikan pentingnya pelestarian lahan pertanian dan peningkatan partisipasi tenaga kerja sebagai kunci keberlanjutan produksi padi di daerah ini.